Sub-high Temperature and High Light Intensity Induced Irreversible Inhibition on Photosynthesis System of Tomato Plant (Solanum lycopersicum L.) - Lu, Tao; Meng, Zhaojuan; Zhang, Guoxian; Qi, Mingfang; Sun, Zhouping; Liu, Yufeng; Li, Tianlai (Frontiers in Plant Science, 2017)
High temperature and high light intensity is a common environment posing a great risk to organisms. This study aimed to elucidate the effects of sub-high temperature and high light stress (HH, 35°C, 1000 μmol∙m-2∙s-1) and recovery on the photosynthetic mechanism, photoinhibiton of photosystem II (PSII) and photosystem I (PSI), and reactive oxygen (ROS) metabolism of tomato seedlings. The results showed that with prolonged stress time, net photosynthetic rate (Pn), Rubisco activity, maximal photochemistry efficiency (Fv/Fm), efficient quantum yield and electron transport of PSII [Y(II) and ETR(II)] and PSI [Y(I) and ETR(I)] decreased significantly whereas yield of non-regulated and regulated energy dissipation of PSII [Y(NO) and Y(NPQ)] increased sharply. The donor side limitation of PSI [Y(ND)] increased but the acceptor side limitation of PSI [Y(NA)] decreased. Content of malondialdehyde (MDA) and hydrogen peroxide (H2O2) were increased while activity of superoxide dismutase (SOD) and peroxidase (POD) were significantly inhibited compared to control. HH exposure affected photosynthetic carbon assimilation, multiple sites in PSII and PSI, ROS accumulation and elimination of Solanum lycopersicum L.